A note on fieldwork in 'dangerous' circumstances: interviewing illegal tiger skin suppliers and traders in Lhasa - Wong, Rebecca W.Y. (International journal of social research methodology, 2015)
Whilst there is no doubt that fieldwork research involving active criminals contains risks and dangers, this is not always the case. Drawing on interviews conducted with illegal tiger skin suppliers and traders in Lhasa (Tibet), this article challenges orthodox understandings of criminological fieldwork. My experience in Lhasa speaks to three methodological issues: (A) the process of gaining access to and recruiting interviewees from the underworld, (B) fieldwork dangerousness and (C) the effects that the personal identity of the researcher has on the process of socialisation with the interviewees.